Coordination Compounds of Co(II), Ni(II) and Cu(II) with Quadridentate Thiosemicarbazone: Their Preparation, Characterization and Structural Investigation - R. Amin, Ragab (Asian Journal of Chemistry, 2010)
New transition metal complexes of Co(II), Ni(II) and Cu(II) with benzil-bis(4-ethyl thiosemicarbazone) and benzil-bis(4-butyl thiosemicarbazone) have been synthesized. Attempts have been made to ascertain their probable structures on the basis of elemental analysis, spectra (lR, electronic), thermal studies and magnetic measurements. The ligands can function as a binegative quadridentate (NSSN) with the metal ions forming complexes in molar ratio 1: 1 having the empitical formulae ML and ML·2H2O. The magnetic moment measurements and the crystal field parameters calculated for Co(II) and Ni(lI) complexes agree fairly well with that reported for known octahedral complexes.